Persatuan dan kesatuan dalam perspektif alquran dan hadits - Hamid, Azwar; Royyan, Muhammad Daniel; Elvaretta, Nazzala Centrinaya; Mubarokah, Ismiatim; Mubarok, M. Najahul; Siregar, Nurhadi (Maliki Interdisciplinary Journal, 2025)
language, customs, arts, religions, and islands. This diversity is expected to be united through the motto Bhinneka Tunggal Ika. Maintaining the unity of Indonesia is a great challenge, which includes maintaining its cultural diversity. Given that Islam is the majority religion in Indonesia, as well as the importance of nationalism and national unity, the nationalism and national unity that every citizen must have, this research aims to explore the values of nationalism in the Hadiths of the Prophet Muhammad. This research refers to primary and primary and secondary books, analyzing the strength of each hadith, and concluding the essence of each hadith. Of each hadith. This type of research is qualitative research with approach, which aims to identify and explore traditions related to nationalism. traditions related to nationalism. This research is divided into two stages: data collection and data management. The research found two main traditions hadiths recorded in the Sahih al-Bukhari, both of which have strong Both are strong and can be practiced. In addition, several other corroborating traditions were also found narrated by Imam al-Tirmidhi, Imam Abu Dawud, Imam Ibn Majah, and Imam Muslim.